(untitled) (Khairulummah, 2022)
Abstract Nikah is an easy and natural means of survival and growth of the human race. And according to Hanafi jurisprudence, engaging in Nikah, i.e. getting married, is better than keeping oneself free for worship. If marriage is an occasion of happiness, then according to the motivation of Islam, more than one marriage is a process of increasing happiness and solving numerous social problems. Which is prevalent since Khair al-Quron. But unfortunately, influenced by the Western propaganda and living with the Hindus for a long time, most of us began to look at outwardly religious matters like remarriage and widow marriage with suspicion and it got to the point that if a person He wants to have more than one marriage, which is his Shariah right, despite the fact of necessity and the observance of the relevant rules and obligations. So it is seen with suspicious eyes in the society. In this article, the historical review of polygamy is to highlight the situation of different countries and the status of polygamy.